10x+5-3x=-6+2x+21

Simple and best practice solution for 10x+5-3x=-6+2x+21 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x+5-3x=-6+2x+21 equation:


Simplifying
10x + 5 + -3x = -6 + 2x + 21

Reorder the terms:
5 + 10x + -3x = -6 + 2x + 21

Combine like terms: 10x + -3x = 7x
5 + 7x = -6 + 2x + 21

Reorder the terms:
5 + 7x = -6 + 21 + 2x

Combine like terms: -6 + 21 = 15
5 + 7x = 15 + 2x

Solving
5 + 7x = 15 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
5 + 7x + -2x = 15 + 2x + -2x

Combine like terms: 7x + -2x = 5x
5 + 5x = 15 + 2x + -2x

Combine like terms: 2x + -2x = 0
5 + 5x = 15 + 0
5 + 5x = 15

Add '-5' to each side of the equation.
5 + -5 + 5x = 15 + -5

Combine like terms: 5 + -5 = 0
0 + 5x = 15 + -5
5x = 15 + -5

Combine like terms: 15 + -5 = 10
5x = 10

Divide each side by '5'.
x = 2

Simplifying
x = 2

See similar equations:

| 3(x-3)-1(x+2)+10=0 | | f(x)=5x-2+x(-6x+10) | | x-10+x-15=x+15 | | y=5x^2+11x+12 | | 2x+2y=3.25 | | 18-2x= | | f(x)=-9x-2+x(-3x+6) | | 7u=-8u+30 | | 6+5(x-2y)= | | 15+6-4*28= | | 12-5*6= | | 5*23+7-62= | | 3*6-4= | | 3n-4=37 | | 54x-1=27x | | 12x^3+14x-48x=0 | | f(x)=In(x^3)(2x^4+1) | | 9+39+22/11-9+3 | | 2x-5(x-4)=-2+3x+4 | | 2x+9=7x-10 | | 5(n+2)=3/5 | | 1x^3+1x^2+c=0 | | (x-4)^(3/2)=16 | | y=4sinx+5 | | 1/2m=28 | | 9p^2+56=18p | | y=-x^2-5x+9 | | 3+2w=8-w | | 2a^2-6a-56=0 | | 2/3p+8=-4 | | 0=2x^2+2x-48 | | 2b-b=2b |

Equations solver categories